The Role Vascular Endothelial Growth Factor, Control Glycemic, Lipid Profile, and Hypoxia-inducible Factor 1-Alpha at Type 2 Diabetic Patients in North Sumatera, Indonesia - Rusdiana, Rusdiana; Widjaja, Sry Suryani; Amelia, Rina; Syarifah, Siti; Rusmalawati, Rusmalawati (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder whose prevalence continues to increase worldwide. Chronic hyperglycemia increases the area of hypoxia that can be measured by markers of hypoxia-inducible factor 1-alpha (HIF-1α) and endothelial cell damage by vascular endothelial growth factor (VEGF) secretion and the association of the course of diabetes mellitus, dyslipidemia is also a risk factor that can aggravate the condition. diabetes mellitus. AIM: The aim of this study was to correlate VEGF with HIF-1α and other metabolic markers in T2DM. METHODS: Examination such as blood pressure, height, and body mass index, and duration of diabetes were recorded. Laboratory examination like blood sugar levels and glycated hemoglobin (Hba1C) levels, lipid profile such as cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and triglycerides were evaluated by Paramitha Laboratory Clinic and VEGF and HIF-1α we examined by ELISA methods in the Integrated laboratory of Medical Faculty, Universitas Sumatera Utara. The study was done by cross-sectional analytic methods, among 135 patients with T2DM who were admitted from the various primary health-care centers in Medan city and surrounding areas in North Sumatera. The inclusion criteria of the samples were all the patients diagnosed with T2DM, both the sexes, and the exclusion criteria of the samples with T1DM and severe disease. The data of the samples were processed using a computer with the SPSS program. RESULTS: There was a positive significant correlation between VEGF with HIF-1α, with a strong correlation, and found a negative correlation between VEGF with fasting blood sugar and HDL (p < 0.005). CONCLUSION: By finding a strong and positive correlation between VEGF and HIF-1α, the sample shows that the increase in VEGF concentration increases in line with the increase in the concentration of HIF-1α and this indicates that the process of angiogenesis in the sample is taking place as a compensatory mechanism of vascular defense.